Water and water-supply : chiefly in reference to the British islands. - Ansted, D. T. 1814-1880 (William H. Allen, 1878)
In the present volume the properties of water and the distribution of surface water are considered, and the author has devoted much space to a description of the various river systems, subordinate as well as principal, throughout the British islands.